Role of twin boundaries on the vortex dynamics in YBaCuO single crystal - Nieva, Gladys; Pastoriza, H.; Candia, S.; Nieva, G. (American Physical Society, 1999)
Fil: Pastoriza, H. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina